Manufacturing silica aerogel and cryogel through ambient pressure and freeze drying. Issue 33 (1st August 2022) - Di Luigi, Massimigliano; Guo, Zipeng; An, Lu; Armstrong, Jason N.; Zhou, Chi; Ren, Shenqiang
Abstract : Ambient pressure and freeze drying techniques enable silica aerogel and cryogel insulation composites. Abstract : Achieving a mesoporous structure in superinsulation materials is pivotal for guaranteeing a harmonious relationship between low thermal conductivity, high porosity, and low density. Herein, we report silica-based cryogel and aerogel materials by implementing freeze-drying and ambient-pressure-drying processes respectively. The obtained freeze-dried cryogels yield thermal conductivity of 23 mW m −1 K −1, with specific surface area of 369.4 m 2 g −1, and porosity of 96.7%, whereas ambient-pressure-dried aerogels exhibit thermal conductivity of 23.6 mW m −1 K −1, specific surface area of 473.8 m 2 g −1, and porosity of 97.4%. In addition, the fiber-reinforced nanocomposites obtained via freeze-drying feature a low thermal conductivity (28.0 mW m −1 K −1 ) and high mechanical properties (∼620 kPa maximum compressive stress and Young's modulus of 715 kPa), coupled with advanced flame-retardant capabilities, while the composite materials from the ambient pressure drying process have thermal conductivity of 28.8 mW m −1 K −1, ∼200 kPa maximum compressive stress and Young's modulus of 612 kPa respectively. The aforementioned results highlight the capabilities of both drying processes for the development of thermal insulation materials for energy-efficient applications.